Tinjauan Fikih Muamalah terhadap Penerapan Service Charge pada Restoran X di Kota Bandung - Ayuningtyas Bastman; Maman Surahman; Siska Lis Sulistiani (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. Sale and purchase is an agreement to exchange objects or goods that have value voluntarily between the two parties in accordance with the agreement of sharia law. In buying and selling there are pillars and shara that must be fulfilled, namely the existence of people who have an agreement (aqid), the existence of shigat (ijab and qabul), the existence of goods or money. The implementation of the sale and purchase of food that occurs at Restaurant X in Bandung City is suspected while there is still one condition that has not been fulfilled, namely his own will (without coercion). The objectives of this study are: First, knowing the Implementation of Service Charge at Restaurant X. Second, to know the Muamalah Jurisprudence Review of the Implementation of Service Charge at Restaurant X. The research method used is qualitative descriptive analysis method. The data used are primary and secondary data. Data collection techniques are carried out by means of literature studies and field research. Based on the results of research that has been conducted by the author are: First, the implementation of the service charge at restaurant x is the absence of prior socialization to consumers. Second, the sale and purchase is still valid, but there is a mild gharar. Abstrak. Jual beli adalah suatu perjanjian tukar menukar benda atau barang yang mempunyai nilai secara sukarela diantara kedua belah pihak sesuai dengan perjanjian hukum syara. Dalam jual beli terdapat rukun dan syara yang harus terpenuhi yaitu adanya orang yang berakad (aqid), adanya shigat (lafaz ijab dan qabul), adanya barang atau uang. Pelaksaan jual beli makanan yang tejadi di Restoran X di Kota Bandung dugaan sementara masih ada salah satu syarat yang belum terpenuhi yaitu Kehendaknya sendiri (tanpa paksaan). Tujuan penelitian ini adalah: Pertama, mengetahui Implementasi Service Charge pada Restoran X. Kedua, mengetahui Tinjauan Fikih Muamalah Terhadap Penerapan Service Charge pada Restoran X. Metode penelitian yang digunakan adalah metode analisis deskriptif kualitatif. Data yang digunakan adalah data primer dan sekunder. Teknik pengumpulan data dilakukan dengan cara studi kepustakaan dan penelitian lapangan. Berdasarkan hasil penelitian yang telah dilakukan oleh penulis adalah: Pertama, pelaksanaan service charge di restoran x ini tidak adanya sosialisasi diawal kepada konsumen. Kedua, jual belinya tetap sah hanya saja terjadi gharar ringan.